THE EFFECT OF GOLD PRICE CHANGES, USD/IDR EXCHANGE RATE CHANGES AND BANK INDONESIA (BI) RATE ON JAKARTA COMPOSITE INDEX (JCI)’S RETURN AND JAKARTA ISLAMIC INDEX (JII)’S RETURN - Robiyanto Robiyanto (Jurnal Manajemen dan Kewirausahaan, 2018)
This study examines the effect of gold price (in Rupiah) changes, US Dollar exchange rate changes against Rupiah (USD / IDR), and BI rate on Jakarta Composite Index (JCI) return and Jakarta Islamic Index (JII) return in Stock Exchange Indonesia during the period of  June 2008 to September 2017. The data used in this study was obtained from the official website of Bank Indonesia and Bloomberg. Data analysis was done by using multiple regression techniques by previously doing classical assumption test. The result of this research is that the exchange rate of USD / IDR changes and BI rate has a significant negative effect on JCI return.